An algorithm for minimum wait draining of two-station fluid re-entrant line - Weiss, Gideon (Annals of operations research, 1999)
In a fluid re-entrant line, fluid moves through a sequence of K buffers, partitioned by their service to I stations. We consider the initial fluid in the system, with no external input. Our objective is to empty all the fluid in the line with minimum total inventory. We present a polynomial time algorithm for this problem, for the case I = 2. [PUBLICATION ABSTRACT]